2012
DOI: 10.1055/s-0032-1329392
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Foreign Bodies: What Is the Current Standard?

Abstract: Rectal foreign bodies represent a challenging and unique field of colorectal trauma. The approach includes a careful history and physical examination, a high index of suspicion for any evidence of perforation, a creative approach to nonoperative removal, and appropriate short-term follow-up to detect any delayed perforation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
194
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(204 citation statements)
references
References 17 publications
4
194
0
6
Order By: Relevance
“…Voluntarily inserted objects include body packers or for sexual erotism while involuntarily inserted objects is seen in rape or abuse victims, and unfortunately commonly affect children. [7] In our study we found that all the patients were male. Kurer et al (2010) in their systematic review of 193 patients observed that 188 were male and 5 were female with a ratio of approximately 37:1.…”
Section: Discussionmentioning
confidence: 47%
“…Voluntarily inserted objects include body packers or for sexual erotism while involuntarily inserted objects is seen in rape or abuse victims, and unfortunately commonly affect children. [7] In our study we found that all the patients were male. Kurer et al (2010) in their systematic review of 193 patients observed that 188 were male and 5 were female with a ratio of approximately 37:1.…”
Section: Discussionmentioning
confidence: 47%
“…If there no evidence of bowel perforation several techniques of extraction may be attempted. Bedside transanal extraction has been reported to be successful in 60-75% of cases [4]. Endoscopic extraction with snare wire may also be attempted which however may not be successful as seen in our case, due to the size of the FB and its shape which prevented an adequate grip with the snare-wire.…”
Section: Discussionmentioning
confidence: 66%
“…Prompt removal of foreign bodies is advisable prior to the development of complications. Removal may be attempted in the ED for objects palpated on per rectum examination and for those that are <10 cm proximal to the anal verge 7. Many authors have recommended an algorithm for management, with a routine approach of initially attempting bedside extraction with local anaesthesia and sedation in patients with no signs of peritonitis.…”
Section: Discussionmentioning
confidence: 99%